Folk Dialogue Sebagai Modal Sosial Dalam Mewujudkan Perdamaian Islam-Kristen Di Maluku - Salakory, Revaldo Pravasta Julian MB (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2020)
Folk dialogue conducted post-conflict serves as social capital for achieving peace in Maluku. Religious dialogue today is often carried out formally by spiritual leaders and government institutions (the elites). During the Christian-Islam conflict, it was realized that society lived in tension, with frequent massacres among people, and religion itself seemed to lose its existence. Religion was perceived as a trigger for the conflict dynamics in Maluku, involving violence between Christians and Muslims, leading to division. This disintegration within the community is evident in daily life, with the emergence of religious identity symbols, such as the terms